Urban agroecology in food and health: home production of sprouts - Guilhon de Castro, Henrique; Marcia Zambom Bertoli de Carvalho, Larissa; de Paula Lopes, Thais; de Andrade Guimarães, Hugo; Gonçalves Di Giuseppe Estanislau, Gabriel (Seven Editora, 2023)
The Sprouts are highly nutritious food and in their production no kind of fertilizer or pesticide is used, using only the reserves stored in the seeds for their growth. Thus, this study aimed to study the rate of accumulation of fresh biomass in the home production of sprouts of five species (Medicago sativa, Trigonella foenum graecum, Vigna radiata, Vigna angularis e Lens culinaris) in five evaluation times (1, 2, 3, 4 e 5 days after the start of the experiment). In the species M. sativa and T. foenum graecum, the method in the presence of light was used. In the species, V. radiata, V. angularis e L. culinaris, the method in the absence of light was used. In the method with the presence of light, the seeds after germination were transferred to a plastic tray where the sprouts were irrigated twice a day. In the method with no light, a glass pot with a capacity of 1 L was used for germination and growth of sprouts, and irrigation was performed once a day. In all species studied, it was observed that fresh biomass increased linearly with the adjustment of the linear regression model. It was found that M. sativa had the highest rate of biomass accumulation and L. culinaris showed the lowest rate of biomass accumulation. From the results obtained in the present study, it was found that the home production of sprouts has a high potential for the supply of quality food for the urban population and can be produced in consumers’ residences with reduced transport costs. DOI: https://doi.org/10.56238/tfisdwv1-021